Overexpressed proteins in hypervirulent clade 8 and clade 6 strains of Escherichia coli O157:H7 compared to E. coli O157:H7 EDL933 clade 3 strain - Amigo, Natalia; Qi, Zhang; Amadio, Ariel; Qunjie, Zhang; Marques da Silva, Wanderson; Baiyuan, Cui; Zhongjian, Chen; Larzabal, Mariano; Cataldi, Angel Adrian; Jinlong, Bei (2017)
Escherichia coli O157:H7 is responsible for severe diarrhea and hemolytic uremic syndrome (HUS), and predominantly affects children under 5 years. The major virulence traits are Shiga toxins, necessary to develop HUS and the Type III Secretion System (T3SS) through which bacteria translocate effector proteins directly into the host cell. By SNPs typing, E. coli O157:H7 was separated into nine different clades. Clade 8 and clade 6 strains were more frequently associated with severe disease and HUS. In this study, we aimed to identify differentially expressed proteins in two strains of E. coli O157:H7 (clade 8 and clade 6), obtained from cattle and compared them with the well characterized reference EDL933 strain (clade 3). Clade 8 and clade 6 strains show enhanced pathogenicity in a mouse model and virulence-related properties. Proteins were extracted and analyzed using the TMT-6plex labeling strategy associated with two dimensional liquid chromatography and mass spectrometry in tandem. We detected 2241 proteins in the cell extract and 1787 proteins in the culture supernatants. Attention was focused on the proteins related to virulence, overexpressed in clade 6 and 8 strains compared to EDL933 strain. The proteins relevant overexpressed in clade 8 strain were the curli protein CsgC, a transcriptional activator (PchE), phage proteins, Stx2, FlgM and FlgD, a dienelactone hydrolase, CheW and CheY, and the SPATE protease EspP. For clade 6 strain, a high overexpression of phage proteins was detected, mostly from Stx2 encoding phage, including Stx2, flagellin and the protease TagA, EDL933_p0016, dienelactone hydrolase, and Haemolysin A, amongst others with unknown function. Some of these proteins were analyzed by RT-qPCR to corroborate the proteomic data. Clade 6 and clade 8 strains showed enhanced transcription of 10 out of 12 genes compared to EDL933. These results may provide new insights in E. coli O157:H7 mechanisms of pathogenesis.